Bacterial infection microenvironment‐responsive porous microspheres by microfluidics for promoting anti‐infective therapy. Issue 1 (16th December 2022) - Gao, Yang; Ma, Qingming
Abstract: The overuse of antibiotics for treating bacterial infection has caused severe bacterial resistance and become a public health threat worldwide. It is desired to develop novel antibiotic delivery systems as efficient antibacterial strategies for promoting anti‐infective therapy. Herein, the AgNPs‐loaded N ‐[(2‐hydroxy‐3‐trimethyl ammonium) propyl] chitosan (HTCC)/hyaluronic acid (HA) porous microspheres (HHPMs) by microfluidics have been developed as novel bacterial infection microenvironment (IME)‐responsive antibiotic delivery systems for promoting antimicrobial therapy. The release of AgNPs can respond explicitly to the IME with acidic pH values and relatively high hyaluronidase concentration. The unique porous structures of HHPMs can effectively facilitate the capture and enrichment of bacteria, thus exerting synergistic antibacterial effects, which can be more efficient in instant bacteria inhibiting and killing. The excellent biocompatibility of HHPMs is revealed by investigating their hemolytic activity and cytotoxicity. In vivo assays demonstrate that the fabricated AgNPs‐loaded HHPMs can effectively resist bacterial infection and promote wound healing and tissue regeneration at infected wound sites by inhibition of the bacterial survival. This work indicates that fabricated HHPMs are ideal bacterial infection microenvironment‐responsive materials for antibiotic delivery and show great promises for promoting anti‐infective therapy in clinics. Abstract : Novel bacterial infection microenvironment‐response porous microspheres for delivering AgNPs have been successfully developed by microfluidics. Generated porous microspheres show responsiveness to the relatively high HAase concentration and acidic pH values in bacterial infection microenvironments to release the loaded AgNPs, and can effectively prevent bacteria from invading and infecting wound, accelerating the healing process of tissue regeneration at wound sites.